2011
DOI: 10.1159/000332012
|View full text |Cite
|
Sign up to set email alerts
|

Metanephros Transplantation Inhibits the Progression of Vascular Calcification in Rats with Adenine-Induced Renal Failure

Abstract: Background/Aim: Recent research has shown that transplanted metanephroi form primitive vascularized kidneys with histologically recognizable renal features. The aim of the present study was to determine the metabolic function of transplanted metanephroi in rats with chronic renal failure (CRF), with particular reference to secondary hyperparathyroidism and vascular calcification. Methods: CRF was induced in 11-week-old male Wistar rats by maintaining them on a 0.75% adenine diet for 4 weeks, followed by normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Previous studies have shown that renal primordial tissues continue to develop in vivo, become vascularized, and exhibit functional properties in neonatal 21 or adult 22,23 recipients. Similar approaches in recipients with different diseases have shown that embryonic kidneys can initiate regenerative processes in damaged kidney tissue, 24 regulate arterial blood pressure, 25 exhibit metabolic properties 26 and prolong life in anephric rats. 27,28 Although these methods showed promising therapeutic potential, they cannot be applied in experiments that seek to grow chimeric organs in vivo for testing the ability of stem cells to contribute to different structures in the organ and modeling human development or disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that renal primordial tissues continue to develop in vivo, become vascularized, and exhibit functional properties in neonatal 21 or adult 22,23 recipients. Similar approaches in recipients with different diseases have shown that embryonic kidneys can initiate regenerative processes in damaged kidney tissue, 24 regulate arterial blood pressure, 25 exhibit metabolic properties 26 and prolong life in anephric rats. 27,28 Although these methods showed promising therapeutic potential, they cannot be applied in experiments that seek to grow chimeric organs in vivo for testing the ability of stem cells to contribute to different structures in the organ and modeling human development or disease.…”
Section: Discussionmentioning
confidence: 99%
“…The embryonic metanephros, with less immunogenic, is a promising potential source for the generation of a functional whole kidney [25]. However, it has been reported that renal proximal tubular cell regeneration is inhibited in a nephrotoxic environment [12,13,[26][27][28]. Consequently, whether embryonic metanephros can grow and differentiate in nephrotoxic environment determines its application prospects in the treatment of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because the metanephroi microenvironment grows under the renal capsule, its protective effect on the kidney is more targeted. Previous studies have determined that metanephroi microenvironment plays an important role in renal regeneration [10,38,39], prevention of vascular calcification [12], maintenance of blood pressure [13], and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average levels of urea nitrogen and creatinine were higher in the cyst fluid that arose from the transplanted tissue than in the sera of the transplanted mice [4]. This also showed that metanephros transplantation can maintain the blood pressure in anephric rats with induced acute hypotension [14] and reduce vascular calcification in rats with chronic renal failure [15], suggesting that transplanted metanephroi have multiple renal functions other than urine production. Although the omentum is used mainly because a tight renal capsule does not confine it, and the host's vessels can be preferentially integrated into the transplant, the low hydrostatic pressure in the omentum may affect the acquisition of some renal function in the developed metanephros.…”
Section: Metanephros Transplantation As a Source Of Organ Regenerationmentioning
confidence: 99%